The big book of hell a cartoon book - Groening, Matt 1954- (HarperCollinsEntertainment, 2004)
Painstakingly assembled and rigorously organized by that master of clutter, Matt Groening, this is not another mini-jumbo, hard-to-read, abbreviated compendium in that seemingly endless series of discourses on hell but a gargantuan historical extravaganza of ten years' worth of the everpopular "Life in Hell "RM" " cartoon strip, which still mysteriously appears weekly in several hundred newspapers tricoastally. Read the whole story of "Life in Hell "RM" ," from early prehistory to late last night
Keywords: Monolog; Bitterkeit; Hase; Comic